Electrocaloric effect in KH₂PO₄ family crystals - Vdovych, A.S.; Moina, A.P.; Levitskii, R.R.; Zachek, I.R. (Condensed Matter Physics, 2014)
The proton ordering model for the KH₂PO₄ type ferroelectrics is modified by taking into account the dependence of the effective dipole moments on the proton ordering parameter. Within the four-particle cluster approximation we calculate the crystal polarization and explore the electrocaloric effect. Smearing of the ferroelectric phase transition by a longitudinal electric field is described. A good agreement with experiment is
obtained. В моделi протонного впорядкування для кристалiв типу KH₂PO₄ враховано залежнiсть ефективних дипольних моментiв вiд параметра протонного впорядкування. В наближеннi чотиричастинкового кластера розраховано поляризацiю кристалiв та дослiджено електрокалоричний ефект у них. Описано розмивання сегнетоелектричного фазового переходу поздовжним електричним полем. Отримано добре узгодження з експериментальними даними.